O despertar da mulher negra: processos de lutas e existências - Carneiro, Gleicy Borges (Universidade Federal do Tocantins, 2023)
This work reports a research aimed at understanding and when the insight into female blackness occurs, as well as what are the most favorable social conditions for such an event. Interest in this topic arises from the following question: What are the social aspects that prevent the instantaneous perception of being a black person, unlike what happens to white people? To reach the conclusion of guiding questions such as this, the present work resorts to bibliographical research, seeking dissertations, theses and scientific articles that have reports, memories and narratives of black women who have experienced what has been called “awakening to their own blackness”. In addition to bibliographic materials, music and other manifestations with potential to express production processes in black women will be consulted. This methodological strategy has the strategy of covering the complexity inherent to the subjective processes associated with the research participants, considering that each experience is uniquely felt in each woman. In addition, it is worth noting that in the proposal here we seek to carry out analyses, reflections and debates based on concepts and theoretical constructions arising from approaches such as: psychoanalysis, socio-historical psychology and, obviously, from the insights and problematizations made by intellectuals and for black intellectuals who are so important for the production of knowledge about the racial issue, such as: Grada Kilomba, Lélia Gonzales, Neusa Santos, Djamila Ribeiro among others and others. Even knowing the impossibility of a process as complex as the awakening to blackness to be grasped and explained by an approach or theory circumscribed to the domain of academic-scientific knowledge, the aim is to bring together concepts and theoretical constructs thought of and used as tools capable of guide the analytical and discursive production proposed by the research. Furthermore, in this way, we can infer some of the possible factors that challenge this issue, such as: racism, whitening policies, exclusion processes and other forms of subjection imposed on black women. Given the above, the work brings to the debate the complexity linked to the recognition and construction of one's own identity and the production associated with the awakening of black women.